2018
DOI: 10.14419/ijet.v7i4.5.20194
|View full text |Cite
|
Sign up to set email alerts
|

Viscous Dissipation and Dufour Effects on MHD Free Convection Flow Through an Oscillatory Inclined Porous Plate with Hall and Ion-Slip Current

Abstract: In this paper the viscous dissipation and Dufour effects on Unsteady MHD free convective flow through a semi-infinite Oscillatory porous inclined plate of time dependent permeability with Chemical reaction and Hall and Ion-Slip Current in a Rotating System was investigated. The dimensionless governing equations for this investigation are solved analytically by using multiple regular perturbation law. The effects of different parameters on velocity, temperature and concentration fields are shown graphically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Subject to the boundary conditions (Ref: Rita Choudhury et al [32]) are Domesticating the non-dimensional quantities, we get Substituting (15) in Eqs. (10)-(13), we get the following governing equations which are dimensionless:…”
Section: Concentration Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…Subject to the boundary conditions (Ref: Rita Choudhury et al [32]) are Domesticating the non-dimensional quantities, we get Substituting (15) in Eqs. (10)-(13), we get the following governing equations which are dimensionless:…”
Section: Concentration Equationmentioning
confidence: 99%
“…In the above examination, viscoelastic fluid was not contemplated. The impact of thermal radiation and Dufour on MHD Casson fluid model and Newtonian fluid flow through non-parallel oscillatory permeable plate with Hall and ion-slip current was examined by Rajakumar et al [31] (non-Newtonian fluid), Rajakumar et al [30], Rajakumar et al [32] (Newtonian fluid). Rajakumar et al [33] and [34] investigated the influence of thermal radiation and Rivlin-Ericksen fluid model on MHD flow with chemical reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the influence of viscous dissipation on steady MHD CF flow past an infinite nonparallel absorbent plate by means of ohmic heating was scrutinized by Rajakumar et al 46 Most recently, Rajakumar et al 47 have explored the influence of spanwise consinusoidally fluctuating temperature as well as viscous dissipation on MHD flow along with radiation absorption. Rajakumar et al 48 discussed viscous dissipation as well as Dufour's effects on MHD oscillatory inclined porous plate. Rajakumar et al 49 reported viscous dissipation on non‐Newtonian MHD fluid flow by means of radiation absorption as well as chemical reaction.…”
Section: Introductionmentioning
confidence: 99%
“…As reported in the literature, the term MHD takes place in the momentum equation while viscous dissipation is in the energy equation. Significance of viscous dissipation on MHD free convective fluid flow through inclined porous plate was considered by Rajakumar et al 17,18 Rajakumar et al 19 considered viscous dissipation and Dufour effects on MHD free convection fluid flow through a vertical Oscillatory porous plate with ion-slip current and radiation absorption. Omamoke et al, 20 Srinivasa Raju et al, 21 Suneetha et al, 22 Jithender Reddy et al, 23 Sivaiah et al, 24 Rajakumar et al, 25 and Rao et al 26 explained the significance of viscous dissipation on MHD fluid past a vertical porous plate.…”
Section: Introductionmentioning
confidence: 99%